The Moderating Role of Dividend Payout Ratio on Price of Book Value - Paramita, Patricia Dhiana; Adhi, Daniel Kartika; Nurkholik, Nurkholik (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
Thel purpose ofl this researchl is tol examine andl analyze thel influence ofl Debt tol Equity lRatio, Currentl Ratio andl Return onl Assets partially onl Price of Bookl Value and thel role ofl on Pricel of Bookl Value and thel role of Dividend Payout Ratio in moderating thel influence ofl Debt tol Equity lRatio, Currentl Ratio andl Return onl Assets onl Price of Bookl Value.Thel research object is Food and Beverage Companies listedl on thel Indonesia Stockl Exchange froml 2020 tol 2024. Al population ofl 100 was selectedl using purposive sampling, resultingl in 16 companies. Datal analysis wasl performed usingl multiple linearl regression andl Moderated Regressionl Analysis (lMRA).Thel results ofl the study showl that Debtl to Equityl Ratio, Currentl Ratio andl Return onl Assets partially havel a positivel and significant effectl on Pricel of Bookl Value. The findings of the moderation test prove that the Dividend Payout Ratio strengthens thel influence ofl the Debtl to Equityl Ratio, Currentl Ratio andl Return onl Assets onl Price of Bookl Value. Inl conclusion, Price of Book Value can be achieved by Food and Beverage Companies by improving thel Debt tol Equity lRatio, Currentl Ratio andl increasing Returnl on lAssets, so that itl can attract investors tol invest and inl decision making and dividend policies pay attention to financial flexibility in achieving good company performance for both internal and external parties.